Highly permselective contorted polyamide desalination membranes with enhanced free volume fabricated by mLbL assembly - Shaligram, Sayali; Shevate, Rahul; Paul, Siddhartha; Shaffer, Devin L. (ACS Applied Materials & Interfaces, 2025)
The permeability-selectivity trade-off in polymeric desalination membranes limits the efficiency and increases the costs of reverse osmosis and nanofiltration systems. Ultrathin contorted polyamide films with enhanced free volume demonstrate an impressive 8-fold increase in water permeance while maintaining equivalent salt rejection compared to conventional polyamide membranes made with m-phenylenediamine and trimesoyl chloride monomers. The solution-based molecular layer-by-layer (mLbL) deposition technique employed for membrane fabrication sequentially reacts a shape-persistent contorted diamine monomer with a trimesoyl chloride monomer, forming highly cross-linked, dense polyamide networks while avoiding the kinetic and mass transfer limitations of traditional interfacial polymerization. The mLbL process allows precise nanoscale control over polyamide selective layer thickness, network structure, and surface roughness. The resulting controlled film thicknesses enable direct measurements of water and NaCl permeabilities. The permselectivities of contorted polyamide membranes surpass those of commercial desalination membranes and approach the reported polyamide upper bound. Solution-diffusion transport modeling indicates that this high permselectivity may be attributed to enhanced water transport pathways in the contorted polyamides that increase water diffusivity-permeability while maintaining high solute rejection through solubility-selectivity.
Keywords: Desalination; molecular layer-by-layer assembly; permselectivity; polyamide; polymers of intrinsicmicroporosity; triptycene; Troger's base

Optimisation of metallic bismuth nanoparticle supported Pt-Bi(x%)/C hybrid electrocatalyst for cost effective and efficient hydrogen production in alkaline media - Dokhe, Revati; Ugale, Atul; Dube, Onkar; Varpe, Vaibhav; Galave, Chaitanya; Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Kumar, Ajay; Husale, Sudhir; Natu, Varun; Shevate, Rahul; et al. (International Journal of Hydrogen Energy, 2025)
The present study employed a simple mechanochemical method followed by 24-h ultrasonication to synthesize oxide-free metallic bismuth (Bi) nanoparticles. This was further used to synthesize a Pt-Bi(x%)/C (NC-x) hybrid electrocatalyst for the hydrogen evolution reaction in alkaline media. X-ray photoelectron spectroscopy and contact angle measurements reveal, Bi modifies the electronic structure and surface morphology of the Pt/C electrocatalyst, thus enhancing reaction kinetics and active site availability. The relative three-electrode study reveals that optimised NC-20 electrocatalyst reduces the overpotentials by 10.44 % and enhances the current density by 53 % compared to commercial Pt/C. The practical applicability of the NC-20 electrocatalyst was studied with the 13 cm2 single cell anion exchange membrane electrolyser. The catalyst demonstrates promising performance where the current density of NC-20//IrO2 relatively increases by 22.6 % compared to standard Pt/ C//IrO2, and shows continuous production and stable performance when monitored for 30 h.
Keywords: AEM; Bismuth nanoparticles; electrocatalyst; Full cell electrolysis; hydrogen evolution reaction; water electrolysis

Metal films from a single source and their application in nanoporous filtration synthesis, electromagnetic interference shielding, and electroadhesion - Veerasubash, Muthupandi; Birajdar, Sarika Hanamant; Kika, Sharmin Percy; Senthilkumaran, Marimuthu; Deshpande, Karan; Shevate, Rahul; Krishnamoorthy, Kothandam (ACS Omega, 2026)
Electroless metal depositions are carried out by a series of reduction steps involving multiple metal ions to obtain a film on synthetic and natural substrates. Herein, we report the use of metal ions from a single element to deposit metal films on various substrates. In a typical metal deposition procedure, Pd2+ ions are anchored on a polycarbonate membrane with vertically aligned pores of 0.6 mu m, which was reduced to its nanoparticles by sodium borohydride. The Pd nanoparticle-modified membrane was then immersed in a Pd plating bath. The Pd2+ ions are reduced by the reducing agent present in the plating bath. The reaction is catalyzed by the Pd nanoparticles. The Pd-modified membrane with vertically aligned Pd tubes were used to convert p-nitrophenol to p-aminophenol, which is an important molecule in the production of acetaminophen. While filtering the reactants through the Pd tubes, due to increased collision between the reactants and the catalyst Pd tubes, 100% conversion is achieved within 5 min. On the contrary, the conversion is only 10% if the membrane is placed in a vessel comprising the reactants. Due to the versatile nature of the metal deposition procedure, nickel was deposited on cotton substrates by a similar procedure. The nickel film-coated cotton cloth showed an impressive electromagnetic shielding interference efficiency of -60 dB while the uncoated cotton cloth did not shield electromagnetic radiation. To demonstrate the versatility of the approach, Pd-coated synthetic polymeric substrates are used to electroadhere gels and gel-like substances. Nickel-coated substrates are not suitable for electroadhesion; hence, a conjugated polymer was deposited on the substrate to electroadhere gel-like substances.

Photoluminescence decay lifetime study of hydrothermally synthesized highly porous ruthenium-silica composite for optical dissolved oxygen sensing application - Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Pandya, Rinu; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Vanka, Kumar; Saha, Avishek; Kanawade, Rajesh (ACS Applied Nano Materials, 2026)
Pore size and surface area of photoluminescence (PL)-based transition metal composites play crucial roles in facilitating oxygen diffusion, thereby enhancing the response and sensitivity of optical dissolved oxygen (DO) sensors. In this study, we successfully applied the hydrothermal method to synthesize a porous ruthenium composite embedded in a silica matrix, demonstrating its effectiveness for optical DO sensing applications. The ruthenium-silica (Ru-Si) composites were synthesized using Ru(bpy)3 2+ and tetraethyl orthosilicate (TEOS) as precursors, with reaction temperatures ranging from 120 degrees C to 200 degrees C over a fixed duration of 4 h. The structural, morphological, and compositional characterization techniques confirmed the successful synthesis and evaluated the porosity, surface features, and chemical structure of the resulting composites. The optimized Ru-Si composite exhibited the highest porosity, characterized by a specific surface area of 996.78 m2 g- 1, and exhibited the highest decay lifetime of 8.14 mu s in deionized (DI) water, compared to other composites. Importantly, we demonstrate an excellent linear response of the synthesized Ru-Si composite to DO concentrations ranging from 2.58 to 11.16 mg L-1, with a Stern-Volmer constant of 0.12. Furthermore, a density functional theory study was conducted to investigate the electronic transitions and to elucidate the oxygen quenching mechanism of the excited Ru composite with molecular oxygen. The calculated photophysical parameters of the composite show good agreement with the experimental results. Preliminary results suggest that the synthesized Ru-Si with high pore size and surface area could be an efficient and effective composite for use in DO sensing applications.
Keywords: Hydrothermal method; opticalDO sensor; oxygen quenching; photoluminescent; ruthenium composite

Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane